Analysis of Coupled Oceanic and Atmospheric Preconditioning for Primary Madden‐Julian Oscillation Events Across ENSO Phases. Issue 9 (1st September 2020) - Shoup, Casey G.; Roman‐Stork, Heather L.; Subrahmanyam, Bulusu
Abstract: The Madden‐Julian Oscillation (MJO) is the dominant mode of air‐sea interaction over intraseasonal timescales. The effects of the MJO are well understood, but the initiation of the MJO remains less conclusive, particularly under El Niño Southern Oscillation (ENSO) conditions. Primary MJO events are those not immediately preceded by existing MJO activity of sufficient strength. As they are rare by definition, primary MJOs remain difficult to study, especially so when observations of events are scarce and of low spatiotemporal resolution. The advent of satellites allows for more expansive observations to be made more frequently than in situ methods, thus improving the observational capabilities of pre‐primary MJO conditions in the ocean and atmosphere. We examined oceanic and atmospheric intraseasonal signals preceding two primary MJO events during contrasting ENSO events in an attempt to bridge the connection between oceanic and atmospheric observations as potentially coupled trigger mechanisms. Satellite observations and model simulations of the central and western Indian Ocean show that intraseasonal peaks in absolute dynamic topography (ADT) and sea surface temperature (SST) upward of 1 to 2 weeks prior to the observed outgoing longwave radiation (OLR) minimum. Surface ocean warming moistens the near surface through anomalous surface fluxes, which destabilizes the lower atmosphere to deep convection. Low‐level moisture flux convergence (MFC) moistens the lower atmosphere prior to convective initiation, thus forcing an increase of total column moist static energy (MSE). Coupled midtropospheric cooling is observed that further destabilizes the atmosphere. Zonal shifts in contributing initiating parameters are observed during ENSO phases. Plain Language Summary: As an eastward propagating band of alternating strong and weak convective activity, the Madden‐Julian Oscillation (MJO) dominates tropical Indian Ocean intraseasonal variability. The initiation of the MJO is heavily debated, although evidence suggests that the ocean and the atmosphere both play a significant role in contributing to the initiation of MJO events. By examining the ocean and atmosphere simultaneously using satellite observations and model output, we can determine relative preconditioning in the ocean and atmosphere and how those signals contribute to MJO convective growth. Although the atmospheric signals in moisture availability are more robust, intraseasonal variability in ocean heat content and sea surface temperature create the conditions necessary for primary MJO initiation in the atmosphere. Air‐sea coupling relative to the initiation of primary MJO events over the tropical Indian Ocean is evident in both satellite observations and model output with observed variability across El Niño and La Niña phases. It is critical that we understand how primary MJO events and ENSO phases interact in order to improve the forecasting and monitoring of these events in the Indian Ocean. Key Points: Atmospheric destabilization is coupled with surface ocean warming ENSO phases contribute to variability of primary MJO initiation La Niña conditions slow down MSE growth over the Indian Ocean